Bovine neutrophils form extracellular traps in response to the gastrointestinal parasite Ostertagia ostertagi. Issue 1 (December 2018) - Mendez, Jonatan; Sun, Donglei; Tuo, Wenbin; Xiao, Zhengguo
Abstract Ostertagia ostertagi (OO) is a widespread parasite that causes chronic infection in cattle and leads to annual losses of billions of dollars in the cattle industry. It remains unclear why cattle are unable to mount an effective immune response despite a large influx of immune cells to the infected abomasal mucosa and draining lymph nodes. Neutrophils, the immune system's first responders, have the capacity to release neutrophil extracellular traps (NETs) to contain various pathogens, including some parasites. In the present study, the mechanisms by whichO .ostertagi influences bovine NET formation were investigated.O .ostertagi larval soluble extract (OO extract) was able to induce typical NETs by purified neutrophilsin vitro, confirmed by co-localization of extracellular DNA with typical NET-associated proteins histone and neutrophil elastase (NE). Consistent with existing literature, inhibition assays demonstrated that these OO extract-induced NETs were dependent upon the enzymes NADPH oxidase and myeloperoxidase (MPO). Live OO stage 4 larvae (L4) stimulated neutrophils to form NETs similar to those induced by OO extract. Bovine neutrophils also released NETs in response toCaenorhabditis elegans, a free-living soil nematode, suggesting that bovine NET production may be a conserved mechanism against a broad range of nematodes. This is the first report demonstratingO .ostertagi -induced NET formation by bovine neutrophils, a potentially underappreciated mechanism in the early immune response against nematode infections.